(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides an in-depth overview of the system of English consonant phonemes, focusing on their classification, articulation, and role in language structure. The article divides consonants into categories based on place of articulation (e.g., bilabial, alveolar), manner of articulation (e.g., plosives, fricatives), and voicing (voiced vs. voiceless). It outlines the 24 consonant sounds in English, providing examples for each, and emphasizes the importance of mastering these sounds for effective communication. The article also highlights challenges that non-native speakers may face, such as unfamiliar phonemes and complex consonant clusters. The conclusion reiterates the significance of understanding consonants for fluency in English and encourages consistent practice. This article is valuable for linguistics students, English learners, and those interested in phonetics, offering both a clear explanation of English consonant sounds and practical insights for language acquisition.